2016
DOI: 10.2147/copd.s119448
|View full text |Cite
|
Sign up to set email alerts
|

Dietary vitamin C intake protects against COPD: the Korea National Health and Nutrition Examination Survey in 2012

Abstract: BackgroundVitamin C, as an antioxidant, has recently been suggested to provide protection against COPD; however, only few national cohort studies have investigated these effects. We aimed to confirm the protective effects of vitamin C against COPD in Korean patients.Patients and methodsWe analyzed the data of 3,283 adults aged ≥40 years (representing 23,541,704 subjects) who underwent pulmonary function tests and responded to questionnaires on smoking history and vitamin C intake, with stratification variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 27 publications
(28 reference statements)
1
19
0
1
Order By: Relevance
“… 35 Additionally, Shin et al reported that Korean smokers with adequate vitamin C intake had acceptable pulmonary functions 36 and Park et al showed that dietary vitamin C provides protection against COPD. 37 Additionally, Morabia et al identified that airway obstruction was reduced by vitamin A in smokers. 11 …”
Section: Discussionmentioning
confidence: 99%
“… 35 Additionally, Shin et al reported that Korean smokers with adequate vitamin C intake had acceptable pulmonary functions 36 and Park et al showed that dietary vitamin C provides protection against COPD. 37 Additionally, Morabia et al identified that airway obstruction was reduced by vitamin A in smokers. 11 …”
Section: Discussionmentioning
confidence: 99%
“…There are many ways in which vitamin C, along with its antioxidant partners, glutathione, vitamin E, vitamin A, and plant-based phytonutrients, affects lung health. It is well established that increased levels of vitamin C in the diet improve health outcomes for smokers and their offspring, as smoking depletes vitamin C [75,76]. Vitamin C is also helpful in fighting infectious diseases such as respiratory infections and pneumonia, COPD regardless of smoking status, asthma, and lung cancer [77].…”
Section: Vitamin Cmentioning
confidence: 99%
“…A, C ve E vitamini gibi antioksidan özelliği bulunan antioksidanların KOAH üzerinde semptom giderici etkileri olduğu gibi pulmoner fonksiyonları da geliştirici özelliği mevcuttur (Park et al, 2016). Ayrıca yaşlanmayla birlikte vücutta artan oksidatif stresin azaltılmasında da yaşlı beslenmesinde önemli bir yer tutmaktadır (Akila, Harishchandra, D'souza, & D'souza, 2007).…”
Section: Vitamin Ve Minerallerunclassified